Benchmarking, knowledge inertia, and knowledge performance in different network structures. Issue 5 (27th May 2020) - Tsai, Sang-Bing; Wu, Wenqing; Ma, Saixiang; Wu, Chia-Huei; Zhou, Bowen
ABSTRACT: A simulation approach is employed to examine the relationship between benchmarking and OKP, and how knowledge inertia in benchmarking influences OKP in different network structures. Results suggest that quick benchmarking (low knowledge inertia) and moderate mutual learning produce higher short-term OKP. Slow benchmarking (high knowledge inertia) and moderate mutual learning achieve higher long-term OKP. OKP performs better in scale-free networks than in small-world networks in the short period. However, in the long period, OKP is higher in small-world networks. Findings guide managers' efforts in choosing the most suitable benchmarking and also suggest that managers should not ignore knowledge inertia.